Effect of irrigatation, rainfed conditions and nitrogen sources on newly released upland rice cultivar (BRS Esmeralda) with greater tolerance to drought stress - Peres, Amanda Ribeiro [UNESP]; Rodrigues, Ricardo Antônio Ferreira [UNESP]; Portugal, José Roberto [UNESP]; Arf, Orivaldo [UNESP]; Gonzaga, Alex Rangel [UNESP]; Meirelles, Flávia Constatino [UNESP]; Garcia, Nayara Fernanda Siviero [UNESP]; Corsini, Daiene Camila Dias Chaves [UNESP]; Takasu, Anderson Teruo [UNESP] (Southern Cross Publishing, 2018)
The rationalization of water use, the increase in productivity and the reduction of nutrient losses are among the current challenges of agriculture. Recently, the upland rice cultivar BRS Esmeralda with more tolerance to drought was released. Thus, the objective of this study was to evaluate the hydric variation and nitrogen sources in topdressing in upland rice cultivar BRS Esmeralda. The experiment was conducted at the Education and Research Farm of UNESP located in Selvíria, Mato Grosso do Sul (MS) state, in 2013/14 and 2014/15. The experiment was conducted in the field under randomized blocks with a split-plot design with three hydric variations as plots (irrigation with a recommended water depth for rice + rainfall; irrigation with 75% of the recommended water depth + rainfall; and without irrigation + rainfall) and four nitrogen sources as subplots (urea, ammonium sulfate, urea + sulfate and coated urea) with four replications. The reduction in water availability delayed the flowering and ripening and reduced the production of dry matter of upland rice. There was a decrease in the productivity of rice grains upon decrease in water availability in the year with incidence of dry spell during the reproductive stage. On the other hand, there was no interference of hydric variation on grain yield in the year with a 14-day water deficit during the vegetative stage. Nitrogen sources provided similar rice productivity. In similar environmental conditions of this work, it is recommended to irrigate upland rice when drought periods occur during the reproductive stage with the recommended depth and N fertilization as topdressing. The topdressing should be carried out with the fertilizer that presents the lowest cost per kg of N.
Keywords: Ammonium sulfate; Coated urea; Grain yield; Oryza sativa L.; Sprinkler irrigation